A spatial approach to measure productivity spillovers of foreign affiliated firms in Turkish manufacturing industries - Mehmet Karaçuka; A. Nazif Catik (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
In this paper we aim to analyze the productivity spillovers of foreign affiliated and domestic firms in Turkish manufacturing industries. As a novelty inter-sectoral linkages are modeled through the use of spatial models. Our results indicate the existence of positive and significant productivity spillovers among the neighborhood firms. We also find that an increase in the share of foreign affiliated firms in a given industry has positive impact on the productivity level of vertically related industries. However, our results do not provide any clear evidence that domestic firms benefit from the foreign affiliated firms either operating in the same industry or in the neighborhood industries. The findings suggest that unlike the effects of foreign affiliated firms, research and development expenditures significantly contribute to the productivity levels of domestic firms.
Keywords: C31; J24; O14; O33; 330; Productivity; foreign direct investment; research and development; spatial econometrics; Produktivität; Spillover-Effekt; Multinationales Unternehmen; Nachbarschaftsökonomie; Lieferanten-Kunden-Beziehung; Schätzung; Türkei